Deworming in pre-school age children: A global empirical analysis of health outcomes - Lo, Nathan C. (PLoS Negl Trop Dis, 2018)
BACKGROUND: There is debate over the effectiveness of deworming children against soil-transmitted helminthiasis (STH) to improve health outcomes, and current evidence may be limited in study design and generalizability. However, programmatic deworming continues throughout low and middle-income countries. METHODOLOGY AND PRINCIPAL FINDINGS: We performed an empirical evaluation of the relationship between deworming in pre-school age children (ages 1–4 years) within the previous 6 months, as proxy-reported by the mother, and health outcomes of weight, height, and hemoglobin. We used nationally representative cross-sectional data from 45 countries using the Demographic and Health Surveys (DHS) during the period 2005–2016. We used logistic regression with coarsened exact matching, fixed effects for survey and year, and person-level covariates. We included data on 325,115 children in 45 STH-endemic countries from 66 DHS surveys. Globally in STH-endemic countries, children who received deworming treatment were less likely to be stunted (1.2 percentage point decline from mean of 36%; 95% CI [-1.9, -0.5%]; p<0.001), but we did not detect consistent associations between deworming and anemia or weight. In sub-Saharan Africa, we found that children who received deworming treatment were less likely to be stunted (1.1 percentage point decline from mean of 36%; 95% CI [-2.1, -0.2%]; p = 0.01) and less likely to have anemia (1.8 percentage point decline from mean of 58%; 95% CI [-2.8, -0.7%]; p<0.001), but we did not detect consistent associations between deworming and weight. These findings were robust across multiple statistical models, and we did not find consistently measurable associations with data from non-endemic settings. CONCLUSIONS AND SIGNIFICANCE: Among pre-school age children, we detected a robust and consistent association between deworming and reduced stunting, with additional evidence for reduced anemia in sub-Saharan Africa. We did not find a consistent relationship between deworming and improved weight. This global empirical analysis provides evidence to support the deworming of pre-school age children.